2021
DOI: 10.1088/1748-9326/abe90b
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and pathways to low-carbon air transport until 2050

Abstract: The COVID-19 pandemic has led to an unprecedented decline in global air transport and associated reduction in CO2 emissions. The International Civil Aviation Organization (ICAO) reacted by weakening its own CO2-offsetting rules. Here we investigate whether the pandemic can be an opportunity to bring the sector on a reliable low-carbon trajectory, with a starting point in the observed reduction in air transport demand. We model a COVID-19 recovery based on a feed-in quota for non-biogenic synthetic fuels that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Governments and policy makers should push these designs now, and bind their funding and implementation to conditions leading towards pandemic-resilient aviation. While the aviation industry has made some improvements in the past decades, for instance, regarding the use of composite materials, synthetic fuels ( Gössling et al, 2021a ), modern manufacturing methods, and turning hardware functions into software, now it is the time to rethink at a larger scale, compared to performing business as usual. If it turns out that existing airlines and equipment manufacturers are reluctant to perform investments and upgrades, there needs to be a better support for novel, less conventional players, be it in terms of funding or certification reliefs.…”
Section: Technological Challengesmentioning
confidence: 99%
“…Governments and policy makers should push these designs now, and bind their funding and implementation to conditions leading towards pandemic-resilient aviation. While the aviation industry has made some improvements in the past decades, for instance, regarding the use of composite materials, synthetic fuels ( Gössling et al, 2021a ), modern manufacturing methods, and turning hardware functions into software, now it is the time to rethink at a larger scale, compared to performing business as usual. If it turns out that existing airlines and equipment manufacturers are reluctant to perform investments and upgrades, there needs to be a better support for novel, less conventional players, be it in terms of funding or certification reliefs.…”
Section: Technological Challengesmentioning
confidence: 99%
“…Non-biogenic synthetic fuels, which require far lower water and land inputs than biofuels, seem to represent the most suitable option for a long-term jet fuel (IEA, 2019a). Their main disadvantage is that to produce these fuels, vast amounts of renewable energy are needed, implying a significant land cost (Gössling, Humpe, Fichert, & Creutzig, 2021). If non-biogenic sustainable fuels are to make a significant contribution to emission reductions, there is also a need to vastly increase production capacity.…”
Section: Low Cost Forest Projectsmentioning
confidence: 99%
“…Low-carbon technologies should be introduced to the field of air transport, such as electric flight and sustainable alternative fuels [118,119]. Gössling et al [120] found that nonbiogenic synthetic fuels likely are the most viable option to completely phase out fossil fuels.…”
Section: Development Of Air Transport After Covid-19mentioning
confidence: 99%